Multi-Institutional Collaborative Resident Education in the Era of COVID-19. Issue 5 (6th September 2020) - Li, Yi; Chu, Carissa; de la Calle, Claire M.; Baussan, Caitlin; Ambani, Sapan N.; Borofsky, Michael S.; Breyer, Benjamin N.; Conti, Simon L.; Hagedorn, Judith C.; Halpern, Joshua A.; Kern, Nora G.; Kielb, Stephanie J.; et al.
Abstract: Introduction: The 2019–2020 coronavirus pandemic has had a significant impact on all aspects of health care. Decrease in clinical and operative volume and limitations for conferences has drastically decreased educational opportunities for resident trainees. We describe the formation and initial success of the Collaborative Online Video Didactics lecture series, a multi-institutional online video didactics collaboration. Methods: Zoom data extraction and postlecture evaluation surveys were used to collect data on the impact of the pandemic on local educational activities as well as feedback about the lecture series. Lectures are being given by faculty from 35 institutions. The twice daily, hour-long webinar averages more than 470 live viewers per session with an average of 33.5 questions per session and has over 7, 000 YouTube views of the recordings after the first 2 weeks. Results: Viewers reported significant decreases in outpatient (75.2%), inpatient (64.9%) and operating room (77.7%) volumes at local programs, and only half (52.7%) of the survey responders indicated an increase in didactics locally. The lectures have been well-received, with over 90% of respondents giving the lecturers and series above average or excellent ratings. A significant majority of responders indicated that the lecture series has allowed for ongoing education opportunities during the pandemic (95.0%), helped to access faculty experts from other institutions (92.3%) and provided a sense of community connectedness during this period of social isolation (81.7%). Conclusions: We strongly encourage other institutions and trainees to participate in the didactic series and hope that this series can continue to evolve and be of benefit beyond the pandemic.